From a Real Place and Real People: Interview with Mississippi Damned Writer/Director Tina Mabry - Moore, Marlon Rachquel (Black Camera, 2011)
Marlon Rachquel Moore interviews emerging independent filmmaker Tina Mabry about her southern upbringing, racial and sexual consciousness, and the joys and turbulence of bringing her first feature-length film, Mississippi Damned, to the silver screen. Mississippi Damned is based on Mabry's family and set in her hometown of Tupelo, Mississippi.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Uplift Cinema: The Emergence of African American Film and the Possibility of Black Modernity - Field, Allyson Nadia (Duke University Press, 2015)
Allyson Nadia Field recovers the forgotten body of African American filmmaking from the 1910s which she calls uplift cinema. These films were part of the racial uplift project, which emphasized education, respectability, and self-sufficiency, and weren't only responses to racist representations of African Americans in other films.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice noir.e; _Nettoyé

Coquie Hughes: Urban Lesbian Filmmaker Introduction to Yvonne Welbon’s Interview with Coquie Hughes - Brody, Jennifer Devere (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Toni Morrison purportedly began her career as a novelist because she noticed a dearth of books about black women. As a result of this limitation, Morrison desired to write books “for people like [her], which is to say black people, curious people, demanding people—people who can’t be faked, people who don’t need to be patronized.”¹ Similarly the writer, director, and filmmaker Coquie Hughes (born Latasha Iva Hughes in Chicago in 1970) has produced narratives that feature an array of queer black women—“Girls Like Us” as she calls them in her web series—who are curious, demanding, flawed, and
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

The Circuitous Route of Presenting Black Butch: The Travels of Dee Rees’s Pariah - Declue, Jennifer (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
At the 2012 Golden Globe awards, during her acceptance speech for the Best Actress award for her performance in The Iron Lady (Phyllida Lloyd, 2012), Meryl Streep gave a shout-out to Adepero Oduye for her role as Alike in Dee Rees’s feature film Pariah (2011). The sentiment behind this esteemed acknowledgment was that brilliant performances in important independent films were overlooked and deserved recognition. Streep would go on to win the Best Actress Oscar for a her portrayal of Britain’s first woman prime minister, the a ultraconservative Margaret Thatcher.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

A Cosmic Demonstration of Shari Frilot’s Curatorial Practice - Rastegar, Roya (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
Shari Frilot is a filmmaker and curator whose creative practice has been driven by sustained explorations of sexuality, technology, desire, cosmic and subatomic structures, mixed-raced identity, and chaos. She has often expressed her modus operandi in the following terms: “It’s impossible to see a cloud when you’re in the middle of it. You have to move outside of the cloud to really get a sense of it.” By continually shifting between the outside and inside of a given framework—whether institutional or personal—Frilot has developed keen modes of challenging conventional structures for understanding and engaging the moving image.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stepping Out on Faith: Interview with Coquie Hughes - Welbon, Yvonne (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
I grew up on the West Side of Chicago, where it was infested with gangs and drugs and violence. But I was always the type of person that wanted to be better than my environment, and I was also the type of person that didn’t want people to underestimate me because of where I came from. And so I made up in my mind, even as a young child, that I wanted to be somebody. I love making movies. I’ve wanted to be who I am ever since I saw Sidney Lumet’s movie The Wiz (1978).
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

“Invite Me In!”: Angela Robinson at Hollywood’s Threshold - White, Patricia (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
In 2005 Angela Robinson released her spy spoof, D.E.B.S. (2004). Robinson first realized the project as the short film D.E.B.S. (2003) through a training program with POWER UP (Professional Organization of Women in Entertainment Reaching Up), the only 501(c)(3) nonprofit film production company and educational organization for women and the GLBTQ community. In 2005 she also became the second black woman and first black lesbian to direct a studio feature, the Disney film Herbie Fully Loaded starring Lindsay Lohan. This moment marked the beginning of the black lesbian media maker hyphenate as Angela Robinson moved to television and began working on The L Word as a writer, director, and eventually producer. Patricia White's essay in this section, "'Invite Me In!': Angela Robinson at the Hollywood Threshold," offers an in-depth exploration of her career trajectory.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Stereotypy, Mammy, and Recovery in Cheryl Dunye’s The Watermelon Woman - Wimbley, Karin D. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The Mammy has been in our field of vision as a popular icon representing black womanhood for more than a century in literature, film, and television and in consumer and material culture.¹ Described as an asexual, rotund slave of older age whose sole responsibility is to take care of her master’s children, Mammy is a beloved character who represents all that is nurturing and maternal. She is dark-skinned and boisterous and thought to have mannish features such as large feet and hands. Mammy wears a large skirt, hiding her sex, and covers her nappy hair with a bandanna or handkerchief.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé

Race-ing Art History: Critical Readings in Reace and Art History - Pinder, Kymberly N (Routledge, 2002)
This comprehensive anthology places issues of racial representation squarely on the canvas. Within these pages are representations of Nubians in ancient art, the great tradition of Westernmasters such as Manet and Picasso and contemporary work by lesser known artists.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Only Skin Deep: Changing Visions of the American Self - Fusco, Coco; Wallis, Brian (Abrams and International Center of Photography, 2003)
"By bringing together a provocative selection of essays and images, Only Skin Deep: Changing Visions of the American Self addresses the issues of nation, race, and selfhood and how they are depicted in ways that are challenging and informative, prompting readers to consider the impact of photography on our everyday lives." "If photographs are chiefly responsible for perpetuating myths of American identity, can a different reading of these representations break down distorting stereotypes? This is the central question posed by Only Skin Deep. The authors in this book forcefully argue that race and nation - and, indeed, photography itself - are fictions, cultural constructions that shape our social interactions. Even as symbols, these photographic depictions of ethnic difference and cultural superiority have very real consequences. This collection of works and essays addresses, for example, the lingering consequences of American colonial expansion; the conflict between public and private visualizations of individuals; the role of commercial imagery in shaping gender roles; the impact of fantasy in ethnic or ethnographic photography; and the uses of science to provide justification for politicized depictions of "race."" "Accompanying a major exhibition of the same name, Only Skin Deep offers a critical rereading of the archive of the history of photography. This applies to the works of famous photographers - such as Dorothea Lange, Walker Evans, Ansel Adams, and Edward Steichen - as well as lesser-known historical figures, including Charles Eisenmann, Frances Benjamin Johnston, Will Soule, and Toyo Miyatake. A substantial part of the book is devoted to contemporary artists and photographers who have moved beyond the multicultural approach to representations of "race" and have made an investigation of the semiotics of cultural identity a prevalent theme over the past decade. Among the recent photographers included are: Nancy Burson, Nikki S. Lee, Glenn Ligon, Paul Pfeiffer, Hulleah Tsinhnahjinnie, Cindy Sherman, Lorna Simpson, and Andres Serrano."--(BOOK JACKET)
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé